Characteristics, Legal Nature and Taxation of Management Contracts According to the Macedonian Law - Zoran Mihajloski; Kristina Misheva (Review of European and Comparative Law)
Managerial contracts are essentially synthesis of the power of management and the power of the leadership of the company. The conclusion of management contracts is not a simple and routine task which the contracting parties will easily access or, on the other hand, they will assign that task to other (third) persons. With the adoption of corporate decisions by the company, at the moment of appointment to the management body, and thus becoming a member of the body, rights and obligations determined by law arise. In the process of transferring the status powers to the management body or the manager, the owners of the companies or their representatives inevitably have to share a part of the power with the elected managers. The managerial contract is an act of free entrepreneurial will of the two parties that conclude the contract. Thus, this contract regulates the salary, allowances, participation in profit, reimbursement for expenses, reimbursement for life insurance, insurable income, and other employment rights and obligations. On the other hand, managers as individuals facing professional risk are to create a professionally based coalition of interests of all those involved in realizing the company’s corporate goals and business policy and thereby enable economic growth and development.